Assessment of iatrogenic damage to adjacent teeth during crown and bridge preparation - Sheikh Bilal Badar; Robia Ghafoor; Muhammad Hasan Hameed; Natasha Anwer (Wolters Kluwer Medknow Publications, 2019)
Introduction: Iatrogenic damage to the adjacent tooth during crown preparation is a frequent disastrous effect. The aim of the study was, therefore, to determine the frequency of different types, degree and location of iatrogenic damage to the adjacent tooth during crown and bridge preparations in a tertiary care setting that lead towards the morbidity of tooth. Materials and Methods: A prospective study was conducted in Aga Khan University dental laboratory in two months period in which a total of 150 dental casts fulfilling the inclusion criteria were analyzed using non-probability convenient sampling technique. The casts were examined using 3.5x magnifying loupes for the location, degree and type of damage to the proximal surface adjacent to the prepared tooth using Moonpar and Faulkner criteria. Data were analyzed by using SPSS version 22. Chi square test was used to assess the association between the experience of practitioner and degree of damage to adjacent tooth. It was also used to determine the association between location of tooth and degree of damage to adjacent tooth. Inter-examiner reliability was assessed by using kappa statistics. Results: A high prevalence of damage to the proximal surface of adjacent teeth (78% on mesial tooth and 60.6% on distal tooth) was observed, with the majority (32.6%) belonging to the mild categories. There were statistically significant associations between the experience of practitioner and the damage to the surface mesial to the preparation. However, more severe damages occurred in mandibular teeth preparations as compared to maxillary teeth preparations. Conclusions: A high frequency of iatrogenic damage to the adjacent teeth had been found during crown and bridge work with the middle of the tooth as the most susceptible site. However, the majority of damages were of milder type including only abrasions.